2022
DOI: 10.3390/antibiotics11040457
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescription Patterns in the Paediatric Primary Care Setting before and after the COVID-19 Pandemic in Italy: An Analysis Using the AWaRe Metrics

Abstract: The containment measures following COVID-19 pandemic drastically reduced airway infections, but they also limited the access of patients to healthcare services. We aimed to assess the antibiotic prescription patterns in the Italian paediatric primary care setting before and after the containment measures implementation. For this retrospective analysis, we used a population database, Pedianet, collecting data of patients aged 0–14 years enrolled with family paediatricians (FP) from March 2019 to March 2021. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
2
10
0
1
Order By: Relevance
“…Concerning the third class of indicators, we decided to describe the ratio between broad spectrum and narrow spectrum molecules using the Amoxicillin/Amoxicillin-Clavulanate index and Access/ Watch index, in the purpose of comparing our research with other ones conducted in similar settings and in the same study period. Two Italian studies based on the Pedianet network recorded from PCPs between 2019 and 2021 showed a reduction in the overall prescriptions ranging from 20% to about 80% (32,33). This data is consistent with the reduction observed in our study population, where the prescription rate dropped by about 65% of pre-implementation.…”
Section: Impact Of the Multifaceted Intervention On The Antibiotic Pr...supporting
confidence: 91%
“…Concerning the third class of indicators, we decided to describe the ratio between broad spectrum and narrow spectrum molecules using the Amoxicillin/Amoxicillin-Clavulanate index and Access/ Watch index, in the purpose of comparing our research with other ones conducted in similar settings and in the same study period. Two Italian studies based on the Pedianet network recorded from PCPs between 2019 and 2021 showed a reduction in the overall prescriptions ranging from 20% to about 80% (32,33). This data is consistent with the reduction observed in our study population, where the prescription rate dropped by about 65% of pre-implementation.…”
Section: Impact Of the Multifaceted Intervention On The Antibiotic Pr...supporting
confidence: 91%
“…Barbieri et al [ 6 ] observed even higher antibiotic prescribing reductions among Italian children compared to the previous paper, with an 80% reduction in antibiotic prescribing rates for children with respiratory tract infections compared to the pre-pandemic period. However, due to uncertainty, pediatricians tended to use more broad-spectrum antibiotics during the first few months of the pandemic, mainly for upper airway infections, such as amoxicillin and clavulanate, at the detriment of first-line antibiotics.…”
mentioning
confidence: 78%
“…While some countries show similar trends to Japan [13,22], in other countries the opposite trend has been observed because of telemedicine consultation resulting in overcautious physicians prescribing more antibiotics when faced with the limited diagnostics available [12,23]. Prescriptions of antibiotics increased in hospitals in some countries during the COVID-19 pandemic because physicians tended to prescribe "prophylactic antibiotics" to hospitalized COVID-19 patients almost by default [14,24,25].…”
Section: Discussionmentioning
confidence: 99%